Societal factors involved on risk mitigation policy - Challenges to seismic retrofitting of hospital buildings - Silva, D. S. (2009)
This paper discusses the recurrent societal problems that emerge in the seismic risk mitigation policy process. It offers a definition of risk mitigation, and examines its application to earthquake threat, particularly the challenges to mitigation adoption and implementation processes. California (E.U.A) experience with the application of legislation (SB1953) mandating seismic structural and non structural retrofitting of hospital facilities illustrates these problems and also shows how stakeholders, who are supposed to act in accordance with the law, have adjusted to the new regulatory environment. This case is illustrative of how well-intended rules may fail in their applicability because of a failure in anticipating undesirable and unintended outcomes. It brings attention to the embeddedness of mitigation efforts on institutional processes, and the importance of taking into account the specificities of target-areas and organizations when investing on seismic safety rehabilitation and retrofitting. / Este artigo discute os problemas de ordem social que recorrentemente emergem na promoção de políticas de mitigação do risco sísmico. Propõe-se uma definição de mitigação do risco, aplicandoa ao caso da ameaça sísmica, e sistematizam-se os principais desafios que se colocam à adopção e implementação de políticas redução da vulnerabilidade sísmica. A experiência da California (E.U.A) na aplicação de um quadro legislativo (SB1953) apostado em promover a readequação estrutural e não estrutural de edifícios hospitalares pretende ser ilustrativo desses mesmos desafios. Neste artigo apresentam-se algumas das estratégias de ajustamento, protagonizadas pelos hospitais, de modo a agir em consonância com o novo regime de regras. Este caso de estudo é revelador de como regras bem intencionadas podem falhar, no terreno, devido à ausência de um esforço prévio de antecipação dos efeitos não-desejados de determinadas medidas. Por outro lado, procura-se, a partir da experiência da Califórnia, chamar a atenção para a importância da adequação de políticas desta natureza às especificidades das organizações a quem competirá a implementação de políticas de reabilitação e de readequação anti-sismica de edifícios.